1873. Pregnancy and Birth Outcomes Among Colombian Women with Zika Virus Disease in 3 Surveillance Sites, Proyecto Vigilancia de Embarazadas con Zika - Honein, Margaret (Peggy) (Open Forum Infect Dis, 2019)
BACKGROUND: Proyecto Vigilancia de Embarazadas con Zika (VEZ) was an intensified surveillance system built upon existing national surveillance of pregnant women with symptoms of Zika virus (ZIKV) disease and conducted in three Colombian cities with a high prevalence of Zika. This analysis of data from VEZ estimates the risk of Zika-associated birth defects among pregnant women with symptoms of ZIKV disease, and among a subset with laboratory evidence of possible ZIKV infection during pregnancy. METHODS: During April–November 2016, pregnant women were enrolled if they were reported to the surveillance system (Sivigila) or visited participating clinics with symptoms of ZIKV disease. Maternal and pediatric data were abstracted from prenatal care, ultrasound, and delivery records, as well as from pediatric or specialist visit records. Available maternal and infant specimens were tested for the presence of ZIKV RNA and/or anti-ZIKV immunoglobulin (IgM) antibodies. RESULTS: Of 1,223 women enrolled, 47.8% and 34.3% reported first or second trimester symptom onset, respectively. Of 381 pregnancies with maternal and/or infant specimens tested, 108 (29%) had laboratory evidence of possible ZIKV infection during pregnancy; half of these (53.3%) were positive for ZIKV RNA only, 37.4% for IgM antibodies only, and 9.3% for both. Of 1,190 of pregnancies with known outcome, 63 (5%) had Zika-associated brain or eye defects; among the subset with any laboratory evidence, 12 (11%) had Zika-associated brain or eye defects. The prevalence of Zika-associated brain or eye defects was 5.9% (35/593) and 4.5% (19/423) among pregnancies with symptom onset in the first and second trimester, respectively. CONCLUSION: Among pregnant women with symptoms of ZIKV disease enrolled during the height of the ZIKV epidemic in Colombia, prevalence of any Zika-associated brain or eye defect was 5%, with a higher prevalence among those with laboratory evidence of possible ZIKV infection. Rapid enhancements to Colombia’s national surveillance enabled the estimation of the risk of birth defects associated with ZIKV disease in pregnancy. DISCLOSURES: All Authors: No reported Disclosures.